2001
DOI: 10.1023/a:1010260612109
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: By computer analysis of the known data bases, we have established that the open reading frames (ORF) coding for proteins that possess high degree of homology with procaryotic DNA-(amino)methyltransferases are present in the genomes of Leishmania major, Saccharomyces cerevisiae, Schizosaccharomyces pombe, Arabidopsis thaliana, Drosophila melanogaster, Caenorhabditis elegans, and Homo sapiens. Conservative motifs typical for bacterial DNA-(amino)methyltransferases are detected in the amino acid sequences of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…This manifested itself in the development of the plastid inner membrane, namely, in intensive TMS formation. Similar effects of antioxidants, particularly ionol, on plant plastids were reported earlier [22,23]. Ionol induced the development of the prolamellar body (a structure unusual for plastids but characteristic of chloroplasts) in plastids of root cells of etiolated wheat (Triticum aestivum L.) seedlings.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…This manifested itself in the development of the plastid inner membrane, namely, in intensive TMS formation. Similar effects of antioxidants, particularly ionol, on plant plastids were reported earlier [22,23]. Ionol induced the development of the prolamellar body (a structure unusual for plastids but characteristic of chloroplasts) in plastids of root cells of etiolated wheat (Triticum aestivum L.) seedlings.…”
Section: Resultssupporting
confidence: 70%
“…It is demonstrated that ambiol influences formation, growth, and development processes in plants [4,5,[14][15][16][17], the content of phytohormones in plant tissues, and activities of H + -ATPase in the plasmalemmata of potato tuber cells [9,[18][19][20][21]. Studies of the effects of individual antioxidants, particularly ionol [22,23] and ambiol [24], on the plant organism were initiated.Genetically transformed (transgenic) plants, e.g., potato plants carrying the gene coding for antimicrobial oligopeptides, so-called defensins, is a promising model for studying the mechanism of ambiol action. It is demonstrated that defensins are capable of protecting plants from phytopathogens [9,25], which is very important for increasing resistance and yield of potato plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By computer analysis of available databases we have established that the open reading frames (ORF) coding for proteins that possess a high degree of homology with prokaryotic DNA (amino)methyltransferases are present in the genomes of Leishmania major, Saccharomyces cere visiae, Schizosaccharomyces pombe, Arabidopsis thaliana, Drosophila melanogaster, Caenorhabditis elegans, and Homo sapiens [100]. Conservative motifs typical for bac terial DNA (amino)methyltransferases have been detect ed in the amino acid sequences of these putative proteins.…”
mentioning
confidence: 99%
“…In mitochondrial genomes including a few fully sequenced higher plant mtDNAs the nucleotide sequences significantly homolo gous to genes of prokaryotic DNA (amino)methyltrans ferases were not found. Thus, ORFs homologous to bac terial adenine DNA methyltransferases are present in nuclei of protozoa, yeasts, insects, nematodes, higher plants, vertebrates, and other eukaryotes [100]. A special search for corresponding proteins and, in particular, ade nine DNA methyltransferases in these evolutionarily dis tant organisms and a study of their functions are quite perspective.…”
mentioning
confidence: 99%